Pasal Penghinaan Presiden Dan Urgensi Pembaharuan Kitab Undang-Undang Hukum Pidana - Oksidelfa Yanto (Nagari Law Review, 2017)
As a state of law, Indonesia highly upholds the legal values existing in societies. By highly upholding the legal values indicates that Indonesian is a nation who abides the law. One of the laws that must be abided by people is criminal law sourced from the Criminal Code or as familiarly known as KUHP. As a positive law Criminal Code (KUHP) is prevailing all over the territorial of Republic of Indonesia and shall be a guide for the entire legal apparatus to impose sanction for violation and crimes. Unfortunately, the Criminal Code which is currently used by the law enforcers as a guide and reference to punish the guilty persons is no longer appropriate with the cultural value of our nation. Actually Criminal Code as the colonial law product is not relevant any longer with the condition of the era and ideology of Indonesian. It is impossible that Indonesia that have been feeling independence for decades but still use the law product of the nation who had occupied it. Consequently, it is urgent that the Indonesian criminal law renewal must be carried out and cannot be negotiable.